(untitled) (Journal of the College of Basic Education, 2022)
When the first government of the United States of America was formed in 1789 headed by George Washington, Alexander Hamilton was chosen as US Treasury Secretary, and the first challenge to this government was the large debts payable, including domestic and foreign debts, and many questioned the government’s ability to pay these debts, and many politicians demanded renunciation About paying these debts, but Alexander Hamilton, who was assigned by Congress to develop a plan to pay these debts, and indeed Hamilton wrote a lengthy report on how to pay these debts at their nominal value, and Hamilton faced opposition from the states of the south led by Thomas Jefferson through a deal to transfer the capital to the south in exchange for approval On a plan, Hamilton has already achieved his goal, which is to pay off the American public debt.